2019
DOI: 10.1007/s00125-019-4952-8
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of familial type 1 diabetes: effects of the relationship to the affected family member on phenotype and genotype at diagnosis

Abstract: Aims/hypothesisIn previous studies, the risk of developing familial type 1 diabetes has been reported to be more than two times higher in the offspring of affected fathers than in those of affected mothers. We tested the hypothesis that index children with an affected father may have a more aggressive disease process at diagnosis than those with other affected first-degree relatives.MethodsA cross-sectional, observational study was performed using the Finnish Pediatric Diabetes Register. Clinical and metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 35 publications
3
40
2
Order By: Relevance
“…However, others have suggested that the breast milk of diabetic mothers should be considered a risk factor for the development of diabetes in children (21). In the present study, the incidence of T1DM in children had a direct relationship with the mothers having diabetes during pregnancy (gestational diabetes), but had no relationship with diabetes in the child's other rstdegree family members, which is consistent with other reports (21,29).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, others have suggested that the breast milk of diabetic mothers should be considered a risk factor for the development of diabetes in children (21). In the present study, the incidence of T1DM in children had a direct relationship with the mothers having diabetes during pregnancy (gestational diabetes), but had no relationship with diabetes in the child's other rstdegree family members, which is consistent with other reports (21,29).…”
Section: Discussionsupporting
confidence: 93%
“…The results show that mother's excess weight during pregnancy decreases the odds of the development of T1DM in the baby. Rasmussen et al in a study showed that, having less than 10.75kg excess weight during pregnancy decreases the risk of T1DM in the child by approximately 17% (29).…”
Section: Discussionmentioning
confidence: 99%
“…However, these previous studies [5,8,12] did not define the degree of family relationships with their PDM subjects. In the current study, we recorded 66.7% rate of DM family history in first-degree relatives which is higher than the rates reported in sub-Sahara Africa and the western populations [24,34].…”
Section: Discussioncontrasting
confidence: 71%
“…Interestingly, having an affected father compared to an affected mother is linked to more frequent severe diabetic ketoacidosis and weight loss in children affected by T1D. Paternal T1D is associated with more severe disease progression [ 102 ].…”
Section: Factors Affecting the Progression Of Autoimmunitymentioning
confidence: 99%